Physical organogenesis of the gut - Chevalier, Nicolas R. (Development (Cambridge), 2022)
The gut has been a central subject of organogenesis since Caspar Friedrich Wolff’s seminal 1769 work ‘De Formatione Intestinorum’. Today, we are moving from a purely genetic understanding of cell specification to a model in which genetics codes for layers of physical–mechanical and electrical properties that drive organogenesis such that organ function and morphogenesis are deeply intertwined. This Review provides an up-to-date survey of the extrinsic and intrinsic mechanical forces acting on the embryonic vertebrate gut during development and of their role in all aspects of intestinal morphogenesis: enteric nervous system formation, epithelium structuring, muscle orientation and differentiation, anisotropic growth and the development of myogenic and neurogenic motility. I outline numerous implications of this biomechanical perspective in the etiology and treatment of pathologies, such as short bowel syndrome, dysmotility, interstitial cells of Cajal-related disorders and Hirschsprung disease.